Pendidikan Karakter Berbasis Hadis Nabi: Aplikasi Nilai-Nilai Akhlak Dalam Kurikulum Sekolah - Chalida (CV. SINAR HOWUHOWU, 2025)
This study aims to examine the potential of the Prophet Muhammad's hadith as an authentic and rich foundation for character education in schools. The issue of moral degradation necessitates a robust and relevant model of character education. Using a qualitative approach with a literature review method, this research analyzes hadith related to moral values such as honesty (sidq), trustworthiness (amanah), compassion (rahmah), justice (′adl), and responsibility (masuliyah). The findings indicate that the hadith are not merely theoretical; they also provide practical narratives and role models that can be systematically integrated into the school curriculum. The proposed conceptual model emphasizes the central role of the teacher as a role model and presents innovative learning strategies to internalize hadith-based values. Despite implementation challenges, this study concludes that the hadith are an invaluable resource for shaping the character of the younger generation, leading to individuals with noble morals and integrity.